Long-term research program for LSAC. - Sanson, A; Morehead, A; Wilson, K; Chevalier, P (My University, 2005)
This paper will provide an overview of the long-term research program for the Longitudinal Study of Australian Children (LSAC). The paper will be based on the outcomes of a workshop to be held in mid-October 2004 involving policy makers from the Commonwealth and State/Territory departments, members of the LSAC Consortium and other leading Australian academics in the area of children's development and wellbeing. The experience of many past large-scale studies is that they have never been fully exploited to address all the questions that could be asked of the data. By developing a research program early in the life of LSAC, we hope to ensure that opportunities to use the data are thoroughly explored prior to the release of the first wave of data in April 2005. The workshop will focus on identifying priority data analysis projects using LSAC data. It will draw on the LSAC research questions and policy priorities to identify discrete and interrelated research projects for the next 5 years. It will include projects based on both the LSAC cross sectional and longitudinal datasets, and identify a mix of cross-discipline and discrete subject matter projects. The research objectives and policy/scientific relevance for each project will be identified and criteria for choosing between projects developed. The projects will be ranked in order of policy and scientific priorities e.g. what do we need to know in the next few years from LSAC for policy development and to address gaps in our knowledge about outcomes and pathways for children. While the resulting program is not intended to exclude analyses of the data to address other questions, it will help guide FaCS, other Government agencies and LSAC consortium members in prioritising research projects and applying for funding.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology